A review of the use of silicone implants in breast surgery. (1st February 2016) - Chao, Albert H.; Garza, Ramon; Povoski, Stephen P.
ABSTRACT: Breast implant surgery is one of the most commonly performed procedures in the field of plastic surgery. While silicone implants are now routinely used in breast surgery, they have previously been the subject of controversy. This was particularly true in the U.S., where there was a moratorium on their use from 1992 to 2006. Following subsequent scientific validation of their safety, silicone implants have re-gained widespread acceptance for clinical use. Modern implant design has aimed to optimize aesthetic outcomes while minimizing implant-related complications, such as capsular contracture and device rupture. One of the most significant advances has been the use of highly cohesive silicone which, through extensive cross-linking, maintains its shape within the body in the presence of physiologic forces. Overall, silicone breast implants are associated with a high degree of patient satisfaction and low rates of complications. Further independent research is necessary to better establish long-term outcomes.